Pengaruh Net Profit Margin (NPM), Return On Investment (ROI), Price To Book Value (PBV), Dan Earning Per Share (EPS) Terhadap Harga Saham Perusahaan Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia - Annisa Widya Fitriyana; Tri Cahyo Nugroho (IJAcc, 2024)
This research aims to determine the influence of Net Profit Margin, Return On Investment, Price to Book Value, and Earning Per Share on the share prices of telecommunications companies listed on the Indonesia Stock Exchange. The sample used in this research was 16 telecommunications companies listed on the Indonesia Stock Exchange. The sampling method used was purposive sampling. Data collection techniques use documentation techniques and literature study. The data analysis technique in this research uses the Multiple Linear Regression Analysis Test, Coefficient of Determination Test, t Test and F Test. Data processing in this research uses SPSS software version 29 for Windows. The results of this research prove that partially the variables Net Profit Margin, Return On Investment, Price to Book Value have no effect on share prices, the Earning Per Share variable has an effect on share prices. Simultaneously, Net Profit Margin, Return On Investment, Price to Book Value, and Earning Per Share have a significant effect on share prices.